Optimalno sledenje sončnih modulov Soncu ob upoštevanju izgub pogonskega sklopa - Seme, Sebastijan (Elektrotehniški vestnik, 2013)
This work deals with the efficiency increase of the photovoltaic (PV) systems. The efficiency of PV systems depends mainly on the solar radiation reaching, the solar module, the efficiency and the types of solar panels, its temperature, DC/DC converter and DC/AC inverter. The efficiency of the solar radiation that reaches the module is the highest when the sunbeams fall aligned with the normal of the module. The influence of the technology and its usefulness is presented in 1, while the impact of the solar cell temperature on the energy conversion efficiency is discussed in 2. The efficiency of the PV systems depends also on the impedance matching. The articles 3 - 5 deal with the determination of the electrical parameters to achieve maximum energy from the PV system through the Maximum Power Point Tracking (MPPT). The efficiency of the PV system can also be increased by the tracking systems. Primarily the one and two-axis tracking systems are used. The authors in 7 - 11 increased the efficiency of the solar energy conversion from 20% to 50% by using the tracking systems compared to the fixed PV systems. The tracking systems use closed- and open-loop control systems. The closed-loop control systems 12 use photo sensors to position the solar panels while the open-loop control systems 13 based on the mathematical algorithm provide predefined trajectories for the tracking systems. Both control systems have imperfections. When the weather is changing, such systems can spend more energy than they gain. This paper presents a new method for determining the optimal trajectories of the open-loop control system of the two-axis sun tracking system (Fig. 1) that assures the maximum efficiency of the solar energy conversion. For the two-axis sun tracking system the energy losses are determined as a function of angle (Figure 2). The aim is to determine the trajectory (tilt beta and aw) of the solar modules where in a specified period the energy production is maximum. To achieve the result a method for predicting the direct and diffuse solar radiation on the Earth's surface in the form of the time dependent function is needed. The mentioned method was already presented in 17. Using the predictions of direct and diffuse solar radiation on the Earth's surface and (1) the solar radiation on the tilt surface is calculated.The angles described in (1) are also shown in Fig. 3. To solve the nonlinear and bounded optimization problem the method called Differential Evolution (DE) 18 is used. In the optimization process the target function is given by (5). Its value is evaluated by calculated prediction of the available solar radiation, the electric drive losses and the efficiency of the PV system. The problem bounds are given in the form of angular speed, lower and upper bounds for the both angles and angle quantization. The results are given for the two-axis tracking system of an active surface 7 m2 and the total efficiency of the PV system Ž = 0.085. The results presented in Figs 4 and 5 show that the trajectory determined by the proposed method gives the best results in terms of the increased energy production of the PV system. In this case the increased energy production compared to the step by step tracking system is not substantial. The ratio may change for the different types and numbers of the solar modules or the different energy consumption of the electric drive.
Keywords: sončne elektrarne; fotonapetostni sistem; optimiranje; sončno sevanje; izgube